Pelindungan Hukum Pengguna Aplikasi Jual Beli Online atas Hilangnya Barang Pesanan saat Menggunakan Jasa Ekspedisi - Syefi Putri Amanda; Anajeng Esri Edhi Mahanani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The Industrial Revolution 4.0 encourages everyone to do routines quickly, easily, and efficiently, activity carried out online that only uses gadgets and networks that may be done anywhere. One example of the application of the industrial revolution 4.0 is the emergence of e-commerce which is also accompanied by the emergence of a term called Marketplace. Marketplace is a market where sellers and buyers meet which there are many products and various kinds of stores, only done online and online. Only with gadgets, ordered goods have been received and delivered by shipping services (expeditions). But with this, it does not rule out the possibility that unpleasant things do not happen such as damage or even loss of ordered goods. With this, this study aims to determine the form of legal protection and legal remedies provided to overcome these problems. This research uses normative research methods through principles, legal rules, etc